2009
DOI: 10.1111/j.1365-2664.2009.01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage and irrigation in cereal fields on weed seed removal by seed predators

Abstract: Summary 1.Agricultural intensification can cause a huge increase in productivity. However, associated costs in terms of reduced, self-regulation and increased reliance on external inputs for the control of pests, diseases and weeds are seldom taken into account or acknowledged. A pro-active approach in which ecosystems services are documented and potential effects of changes in agricultural practices evaluated may lead to more informed decisions prior to implementation. 2. We investigated the effects of manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 22 publications
2
77
3
Order By: Relevance
“…Therefore, unlike in conventional practice of burial that makes weed seeds largely unavailable, seed predation could be important in NT systems where newly produced weed seeds remain on the soil surface and are most vulnerable to surface-dwelling seed predators like mouse, ants and other insects (Hulme 1994;Baraibar et al 2009;. For example, reduced seed input from 2000 to 360 seeds m −2 as a result of post-dispersal predation of barnyard grass ( Echinochloa crus galli P.…”
Section: Weed Seed Bankmentioning
confidence: 97%
See 1 more Smart Citation
“…Therefore, unlike in conventional practice of burial that makes weed seeds largely unavailable, seed predation could be important in NT systems where newly produced weed seeds remain on the soil surface and are most vulnerable to surface-dwelling seed predators like mouse, ants and other insects (Hulme 1994;Baraibar et al 2009;. For example, reduced seed input from 2000 to 360 seeds m −2 as a result of post-dispersal predation of barnyard grass ( Echinochloa crus galli P.…”
Section: Weed Seed Bankmentioning
confidence: 97%
“…was reported by Cromar et al (1999). Further, CA systems may favour population growth of harvester ants by not damaging the nests, and may minimize the redistribution of weed seeds stored in superficial chambers (Baraibar et al 2009).…”
Section: Weed Seed Bankmentioning
confidence: 99%
“…Predation inclination of crop residues in NT viz., corn residue, soybean, and wheat were akin to the other (Cromar et al, 1999). Baraibar et al (2009) also found that NT increased seed predation in cereal production.…”
Section: Weed Seed Predationmentioning
confidence: 90%
“…Lack of soil disturbance via tillage could also encourage higher predator populations. No till fields increase the number, diversity, or activity of seed-consuming fauna as compared to conventionally tilled fields (Blubaugh and Kaplan, 2015) may be due to increased habitat (Baraibar et al, 2009) or decreased mortality rate (Shearin et al, 2007).…”
Section: Herbicidesmentioning
confidence: 99%